Awareness on Heart Diseases among Bangladesh Army Personnel (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Heart diseases are global public health problem. In 2015, 14.31% of total death in Bangladesh was due to coronary heart disease. Moreover in 2016, 2(two) recruits and 1(one) officer of Bangladesh army encountered sudden death due to cardiac arrest.Objective: To ascertain the level of knowledge, awareness and health practice regarding the threat of cardiovascular diseases among Bangladesh Army personnel.Materials and Methods: This cross-sectional observational study was conducted among 242 members of Bangladesh Army in different training centers and school under Army training and doctrine command (ARTDOC), units of 19 infantry division, Battle group of ARTDOC and Head quarter (HQ) ARTDOC, from February to July 2017.Results: Among the respondents, 56.2%, 45% and 44.6% respectively mentioned tobacco smoking, obesity and sedentary life style are the causes of heart disease and 62%, 42%, 31%, 10% and 2% mentioned that chest pain, shortness of breathing, sweating, radiating pain in jaw and extremity and snoring-sleep apnea are the symptoms and signs of heart disease.Conclusion: From the study it was revealed that, majority of the respondents had poor level of knowledge on awareness of heart disease. Adequate effort may be taken to increase the awareness by expert professionals and social media.JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 47-50